(untitled) (Universal International Scientific Journal, 2026)
This thesis discusses the importance of motivation in the online learning process, its impact on students’ learning activities, and its role in increasing educational efficiency. Since the independent learning process of students increases in online learning, "motivation" is an important factor in this process. The research also analyzes the impact of motivation on students’ interest, activity, and level of knowledge acquisition. It also discusses modern pedagogical methods and technologies that serve to increase students’ motivation.